Phosphorus Availability Alters the Effect of Tree Girdling on the Diversity of Phosphorus Solubilizing Soil Bacterial Communities in Temperate Beech Forests - Michas, Antonios; Pastore, Giovanni; Chiba, Akane; Grafe, Martin; Clausing, Simon; Polle, Andrea; Schloter, Michael; Spohn, Marie; Schulz, Stefanie (Frontiers in Forests and Global Change, 2021)
Phosphorus (P) solubilization is an important process for P acquisition by plants and soil microbes in most temperate forests. The abundance of inorganic P solubilizing bacteria (PSB) is affected by the P concentration in the soil and the carbon input by plants. We used a girdling approach to investigate the interplay of root-derived C and initial P content on the community composition of gcd-harboring bacteria as an example of PSB, which produce gluconic acid. We hypothesized that gcd-harboring PSB communities from P-poor sites are more vulnerable to girdling, because of their lower diversity, and that a shift in gcd-harboring PSB communities by girdling is caused by a response of few, mostly oligotrophic, taxa. We used a high-throughput metabarcoding approach targeting the gcd gene, which codes for the quinoprotein glucose dehydrogenase, an enzyme involved in the solubilization of inorganic P. We compared the diversity of gcd-harbouring PSB in the mineral topsoil from two temperate beech forests with contrasting P stocks, where girdling was applied and compared our data to the respective control plots with untreated young beech trees. At both sites, gcd-harboring PSB were dominated by Proteobacteria and Acidobacteria, however with differences in relative abundance pattern on the higher phylogenetic levels. The P-poor site was characterized by a high relative abundance of Kaistia, whereas at the P-rich site, Dongia dominated the gcd-harboring bacterial communities. Girdling induced an increase in the relative abundance of Kaistia at the P-poor site, whereas other bacterial groups of the family Rhizobiaceae were reduced. At the P-rich site, major microbial responders differed between treatments and mostly Bradyrhizobium and Burkholderia were positively affected by girdling in contrast to uncultured Acidobacteria, where reduced relative abundance was found. Overall, these effects were consistent at different time points analyzed after the introduction of girdling. Our data demonstrate that plant-derived carbon influences community structure of gcd- harboring bacteria in temperate beech forest soils.